2020
DOI: 10.1371/journal.pone.0235538
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of delayed first antenatal care booking among reproductive age women in Ethiopia; a multilevel analysis of EDHS 2016 data

Abstract: Background Early or timely initiation of antenatal care and regular visits based on the schedule have a tremendous effect on both maternal and fetal health. Despite the paramount benefits of early initiation of ANC within the first 12 weeks of pregnancy, women still do not have adequate and equal access to high-quality early antenatal care. Objective To determine the prevalence and factors associated with delayed first ANC booking in Ethiopia. Method A secondary data analysis was conducted using the 2016 Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
52
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 40 publications
20
52
3
2
Order By: Relevance
“…The outcome variable of this study was delayed first ANC visit which means mothers who have first ANC booking after 12 weeks of gestational age [ 27 ] which have a binary response. A woman said having delayed first ANC visit if she books her first ANC visit after 12 weeks of pregnancy and coded as “1”, and women said having early first ANC visit if she books her first ANC before 12 weeks gestation and coded it as “0.” [ 4 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome variable of this study was delayed first ANC visit which means mothers who have first ANC booking after 12 weeks of gestational age [ 27 ] which have a binary response. A woman said having delayed first ANC visit if she books her first ANC visit after 12 weeks of pregnancy and coded as “1”, and women said having early first ANC visit if she books her first ANC before 12 weeks gestation and coded it as “0.” [ 4 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Community-level media exposure was assessed by the proportion of women who had at least been exposed to one media. It employs``` “0” to indicate low-level and “1” to indicate high-level media coverage at the community level [ 4 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Moreover, studies at the sub-national and national levels focused on timing and number of ANC visits rather than ANC content and associated factors. [27][28][29][30][31][32][33][34][35] Therefore, this study aimed to identify self-reported received ANC content and associated factors which may aid in designing guidelines and policies to improve maternal health, pregnancy outcomes, and child survival in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little research in this regard is available in the context of Gamo Zone, Southern Ethiopia. Moreover, the few existing studies focussed entirely on prenatal care, urban women or speci c geographical areas [14][15][16][17][18][19].…”
mentioning
confidence: 99%